Free Trade Intervention: Political-Economic Intervention on Global Business Environment - Satryo, Cecillia (APMBA (Asia Pacific Management and Business Application), 2018)
Historically, the arguments for free trade intervention have raised to a simultaneous debate. The essay examines to what extent the political reasons have been used to counter free trade as compared to economic reasons. Some view political reasons as the sole driver to intervene, but typically political-economic are positively correlated. In fact, a country’s intervention to an excessive degree is negative from business point of view. It is recommended that country’s intervention should not exceed certain limit because free trade itself have positive impact on global business environment.